2011
DOI: 10.1016/j.resp.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A neonatal mouse model of intermittent hypoxia associated with features of apnea in premature infants

Abstract: A neonatal mouse model of intermittent hypoxia (IH) simulating the recurring hypoxia/reoxygenation episodes of apnea of prematurity (AOP) was developed. C57BL/6 P2 pups were culled for exposure to either intermittent hypoxia or intermittent air as control. The IH paradigms consisted of alternation cycles of 20.9% O2 and either 8.0% or 5.7% O2 every 120 or 140 seconds for 6 hours a day during daylight hours from day 2 to day 10 postnatally, i.e., roughly equivalent to human brain development in the perinatal pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…There are several reports exploring the role of experimental intermittent hypoxemia in neurologic morbidity associated with adult sleep apnea and apnea of prematurity (Cai et al, 2011(Cai et al, , 2012Douglas et al, 2010;Oorschot et al, 2013;Xu et al, 2004). Similar to our results, studies on neonatal animals demonstrated poorer WM myelination in mice and rats exposed to IH compared to their naïve controls.…”
Section: Discussionsupporting
confidence: 90%
“…There are several reports exploring the role of experimental intermittent hypoxemia in neurologic morbidity associated with adult sleep apnea and apnea of prematurity (Cai et al, 2011(Cai et al, , 2012Douglas et al, 2010;Oorschot et al, 2013;Xu et al, 2004). Similar to our results, studies on neonatal animals demonstrated poorer WM myelination in mice and rats exposed to IH compared to their naïve controls.…”
Section: Discussionsupporting
confidence: 90%
“…The murine model of IH exposures during sleep was used in this study as previous reports (Cai et al, 2011(Cai et al, , 2012b. Briefly, adult mice were exposed to an IH profile designed to produce similar nadir hemoglobin oxygen saturations (50-60%) and apnea/ hypopnea index (21-50 times/h) as observed in moderate to severe OSA patients.…”
Section: Experimental Animals and Ih Exposuresmentioning
confidence: 99%
“…This vulnerability can be intrinsic, caused by excessive glutathione depletion from oxidative stress or extrinsic, caused by glutamate receptor-mediated toxicity, the result of glutamate release by adjacent dying cells (14). Either mechanism sets up a cascade of events, leading to loss of pre-OLs and damage to surrounding white matter (1517). …”
Section: Mechanisms Of Injury—wmimentioning
confidence: 99%